Research on reliability optimization of weapon system based on Generalized Lagrange multipliers - Qiang Guo; Liqiang Jiang; Jianjun Gao; Xuekui Wang; Xia Xiao (2011 International Conference on System Science, Engineering Design and Manufacturing Informatization, 2011)
This paper considered complex weapon system reliability optimization allocation. Firstly, according to the restrictions like cost and quality of the system, this paper constructed the optimization model of reliability redundancy allocation of weapon system with the system reliability as objective function. Secondly, this paper proposed a numerical solving algorithm of Generalized Lagrange multipliers method based on Lagrange multipliers method and Kuhn-Tucker condition. This paper did example analysis about reliability optimization allocation of antiaircraft weapon system.